Robust tumor immunity to melanoma mediated by interleukin-9–producing T cells - Purwar, Rahul; Schlapbach, Christoph; Xiao, Sheng; Kang, Hong Soon; Elyaman, Wassim; Jiang, Xiaodong; Jetten, Anton M; Khoury, Samia J; Fuhlbrigge, Robert C; Kuchroo, Vijay K; Clark, Rachael A; Kupper, Thomas S (Nature medicine, 2012)
In this issue, Thomas Kupper and colleagues report that mice deficient for ROR-γ or interleukin-23 (IL-23) receptor showed impaired melanoma growth. Tumor growth inhibition was dependent in part on IL-9 and T helper type 9 (T H 9) cells. Moreover, the authors showed that IL-9 acts on mast cells rather than T or B cells to mediate its antitumor effects and that T H 9 cells are present in human blood and skin, suggesting that a role for T H 9 cells in human tumor immunity should be explored. Interleukin-9 (IL-9) is a T cell cytokine that acts through a γC-family receptor on target cells and is associated with inflammation and allergy. We determined that T cells from mice deficient in the T helper type 17 (T H 17) pathway genes encoding retinoid-related orphan receptor γ (ROR-γ) and IL-23 receptor (IL-23R) produced abundant IL-9, and we found substantial growth inhibition of B16F10 melanoma in these mice. IL-9–blocking antibodies reversed this tumor growth inhibition and enhanced tumor growth in wild-type (WT) mice. Il9r −/− mice showed accelerated tumor growth, and administration of recombinant IL-9 (rIL-9) to tumor-bearing WT and Rag1 −/− mice inhibited melanoma as well as lung carcinoma growth. Adoptive transfer of tumor-antigen–specific T H 9 cells into both WT and Rag1 −/− mice suppressed melanoma growth; this effect was abrogated by treatment with neutralizing antibodies to IL-9. Exogenous rIL-9 inhibited tumor growth in Rag1 −/− mice but not in mast-cell–deficient mice, suggesting that the targets of IL-9 in this setting include mast cells but not T or B cells. In addition, we found higher numbers of T H 9 cells in normal human skin and blood compared to metastatic lesions of subjects with progressive stage IV melanoma. These results suggest a role for IL-9 in tumor immunity and offer insight into potential therapeutic strategies.